Strategi Guru Pembelajaran Tari di MTs Negeri 1 Kota Prabumulih - Rina Maulidiana; Muhamad Idris (Mahesa Research Center, 2023)
The purpose of this study was to find out how the teacher's strategy in learning dance at MTs Negeri 1 Prabumulih City. The method used in this research is descriptive qualitative, the teacher's strategy in learning dance at MTs Negeri 1 Prabumulih City. The samples used were teachers and students of class VIII 9, totaling 30 students. The technique used is observation, interview and documentation. Based on the results of dance learning activities using scientific teacher learning strategies and using peer tutoring methods in class VIII 9 guided by the activity observation sheet, it shows that the teacher's ability in the dance learning process in cultural arts subjects is categorized as good. Seeing from the evaluation results of observational data analysis, it can be interpreted that the teacher's strategy in learning dance in class VIII 9 Negeri 1 Prabumulih City in learning dance material can be categorized as good.